Improving China’s Global Lithium Resource Development Capacity - Li, Hanshi; Zhu, Ting; Chen, Xiangshun; Liu, Hanbin; He, Guangsheng (Frontiers in environmental science, 2022)
Flourishing sales of new electric vehicles have led to a considerable surge in demand for the vital, upstream raw material, lithium (Li). As an essential energy metal and raw material for the production of batteries, lithium has become indispensable to the electric vehicle industry. It has been identified as a strategic, emerging industrial mineral in China. Based on a literature review and qualitative analysis of the imbalance between the supply and demand of lithium raw materials in China, this paper analyzes the current challenges of China’s lithium supply chain, especially mining, pricing and recycling, that are obstructing the realization of China’s carbon neutrality. On this basis, relevant policy suggestions are proposed from three perspectives: strengthening lithium resource development and reserve capacity, promoting international cooperation for lithium supply, and properly regulating the circular economy of domestic lithium resources.